(untitled) (Research, Society and Development, 2022)
Medicinal plants have a tradition of use as an alternative medicinal treatment for various diseases. Currently, phytotherapy and the use of medicinal plants in the form of tea have been resources used to treat anxiety disorder and contribute to the weight loss process by many people. Therefore, this article aims to present the most used medicinal plants for the aforementioned purposes. Methodology: 17 species were selected from a literature review of the last 15 years, where their applicability, benefits and contraindications for use were researched. Result: the research showed the action of the active principles of plants in humans and mice, and demonstrate a favorable performance to anxiolytic activity and enzymatic activity that contributes to weight loss with medicinal plants. Conclusion: with this study it was possible to identify what there is scientific knowledge about medicinal plants used to treat anxiety disorder and contribute to the weight loss process.